The Style of Paying Attention in Wissam Al-Hasnawi's Poetry - م.م. كوثر شاكر عبد الرضا (Journal of College of Education, 2023)
Attention is one of the most critical creative expressive methods in literary history, as it possesses an effectiveness based on the requirements of deviation and skipping from the usual patterns, through the transmission of speech from one form to another, within literary texts, whether poetry or prose and as a result of what this method reflects from a rhetorical side in the poetic text. It cannot be overlooked, as the research tracked it in Wissam Al-Hasnawi's poetry to demonstrate the artistic and aesthetic significance envisaged through the transformation of the discourse from one form to another, which contributed to achieving specific goals, the most prominent of which is preventing the text from flowing at the same pace and walking in an extended and irregular manner